Characterization of a Mannitol-Utilizing, Nitrogen-Fixing Bradyrhizobium japonicum USDA 110 Derivative - Mathis, James N. (1986)
We have isolated a colonial derivative of Bradyrhizobium japonicum USDA 110 (designated MN-110) that is both mannitol utilizing and N(2) fixing. Derivative MN-110 showed growth on mannitol and glucose similar to that of non-N(2)-fixing, mannitol-utilizing L2-110. Derivative MN-110 showed high constitutive and induced d-mannitol dehydrogenase activity (similar to L2-110) relative to N(2)-fixing, non-mannitol-utilizing I-110. Hybridization to EcoRI and HindIII total DNA digests with cloned USDA 110 nif DK and nif H genes revealed similar patterns for non-N(2)-fixing mannitol-utilizing derivative L1-110 and derivative MN-110. Symbiotic tests with soybean cultivars Ransom and Lee indicate MN-110 to be a superior N(2)-fixing derivative compared with derivative I-110 and the parent strain USDA 110. However, these differences were not revealed when comparing 28-day-old soybean-B. japonicum associations but were apparent in 49-day-old associations. It was apparent from this work that mannitol utilization was not necessarily correlated to symbiotic effectiveness in B. japonicum and that gene rearrangements were not responsible for differences in N(2) fixation between L1-110 or L2-110 and MN-110.